Calibration of Big Bottle RAD H2O set-up for radon in water using HDPE bottles. (May 2015) - De Simone, Gabriele; Galli, Gianfranco; Lucchetti, Carlo; Tuccimei, Paola
Abstract: Glass bottles are generally employed for water sampling because glass is impervious to radon and is not lost during sample storage. On the other hand, glass is fragile and may break, so 1 L High Density PolyEthylene (HDPE) bottles (Thermo Scientific Nalgene) are tested in place of glass vessels employing Big Bottle RAD H2 O device (Durridge Company) coupled with RAD7 monitor. The purpose of this calibration is to quantify radon loss during storage in HDPE bottles, evaluate possible radon uptake by known volume of desiccant (Drierite, granular CaSO4 ) and quantify radon interaction with the rubber and plastic parts of the experimental circuit. These processes have been separately investigated, performing proper experiments for the assessment of their influence on resulting radon data using seven series of solutions at known activity concentrations in the range from 27 to 194 Bq/L. Percent radon loss during storage in 1 L HDPE bottles has been estimated at 0.0045 min −1 . Radon absorption by desiccant, expressed as 'equivalent' volume of Drierite is 0.673 ± 0.092 L and is somehow independent, within errors, from i ) the amount of water already absorbed in Drierite, ii ) a recirculation time greater than 30 min and iii ) radon concentrations. Radon absorption/desorption from rubber and plastic parts of the experimental device has been assessed as a function of concentration gradient between the inner volume of the circuit and the pores of polymer's. A final algorithm accounting for the above described physical processes has been developed for long runs (2–3 h). A simplified calculation method for short measurements (30 min) is also provided. Highlights: Big Bottle RAD H2 O set-up for measuring radon in water was calibrated. Glass bottles were replaced with HDPE vessels because too fragile for water sampling. Radon diffusion coefficient through HDPE was calculated. Radon absorption by Drierite and polymers in the setup was quantified. A calculation model based on a 30 min measurement was developed.